Wahana Edukasi Kreatif Sebagai Sarana Peningkatan Life Skill Siswa SD Bernuansa Alam Desa Darsono - Cahyaningtyas, Cindy Dwi; Widayanti, Ayu; Zahra, Mutiara Shofia; Widayanti, Anis; Miranda, Yussy; Rusdianto, Rusdianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Darsono Village is a village located in Arjasa District, Jember Regency, East Java. The economic condition in Darsono Village is relatively low and exacerbated by low literacy skills. Darsono Village has several potentials, such as empty land, beautiful village atmosphere and various facilities in the village. Therefore, we carry out a service program that focuses on improving the quality of formal education through the program